CO(2) lattice laser reverses skin aging caused by UVB - Wang, Hongyi (Aging (Albany NY), 2020)
The carbon dioxide (CO(2)) lattice laser has been successfully used to treat facial skin photoaging induced by UV light. In this study, we analyzed the effect of CO(2) lattice laser irradiation on skin photoaging, and investigated the underlying mechanisms. Our results demonstrate that the laser promoted collagen synthesis and proliferation of primary human skin fibroblasts, inhibited cell senescence, and induced expression of superoxide dismutase (SOD) and the signaling protein SMAD3. In addition, this laser reversed cell cycle arrest and fibroblast apoptosis induced by UVB irradiation, and restored fibroblast proliferation inhibited by SMAD3 silencing. Using a rat model of photoaging, our results show that the laser increased collagen expression and dermal thickness, demonstrating that the CO(2) lattice laser has a profound therapeutic effect on photoaged skin. Together, our in vitro and in vivo data show that the CO(2) lattice laser can reverse the skin aging caused by UVB, and indicate that this effect is mediated through SMAD3.